Doing Good by Doing Bad: How Tone at the Top and Tone at the Bottom Impact Performance-Improving Noncompliant Behavior - Corinna Ewelt-Knauer; Anja Schwering; Sandra Winkelmann (Journal of Business Ethics, 2020)
This study investigates how tone at the top, implemented by top management, and tone at the bottom, in an employee's immediate work environment, determine noncompliance. We focus on the disallowed actions of employees that improve their own and, in turn, the company's performance, referred to as performance-improving noncompliant behavior (PINC behavior). We conduct a survey of German sales employees to investigate specifically how, on the one hand, (1)~corporate rules and (2)~performance pressure, both implemented by top management, and, on the other hand, (3) others' PINC expectations and (4) others' PINC behavior, both arising from the employee's immediate work environment, influence PINC behavior. When considered in isolation, we find that corporate rules, as top management's main instrument to guide employee behavior, decrease employee PINC behavior. However, this effect is negatively influenced by the employees' immediate work environment when employees are expected to engage in PINC or when others engage in PINC. In contrast, even though top management places great performance pressure on employees, that by itself does not increase PINC behavior. Overall, our study informs practitioners and researchers about whether and how the four determinants increase or decrease employees' PINC behavior, which is important to comprehend triggers and to counteract such misconduct.
Keywords: 300; Noncompliance; Tone at the top; Tone at the bottom; Corporate rules; Performance pressure; Others' expectations; Others' behavior